Low temperature preservation of bovine ovaries on in vitro development of oocytes - Sung Woo Kim; Min Su Kim; Chan-Lan Kim; Dongkyo Kim; Namtae Kim; Hwan-Hoo Seong (The Korean Society of Animal Reproduction and Biotechnology, 2016)
During the ovary preservation in low temperature, the cumulus oocyte complexes(COCs) lose their developmental competences after in vitro fertilization. We used phosphate-buffered saline (PBS) as a basic solutions of at various temperatures (25, 15 or 5 °C) and supplemented them with 1mM glucose and 0.5mM glutamine as a source of carbohydrate metabolites. After recovery of COCs and in vitro fertilization, a significantly higher number of oocytes developed into blastocysts. The developmental competence of embryos that were originated from ovaries preserved at 15 °C was increased compared to those of 25 or 5 °C. The maturation rate of oocytes was not differed between 24 and 36 h at 15 °C but showed lower than control group (71% versus 78%). in vitro-fertilized oocytes from ovaries stored at 25 °C for 24 h or at 5 °C for 24 h had a significantly decreased developmental potentials, but at 15 °C did not (27% versus 29% of blastocysts to develop into day 8). With these results, bovine ovaries can be preserved at 15 °C for 36 h without decreasing developmental capacity of in vitro-fertilized oocyte at least to the blastocyst stage. This information provides valuable information of preserving ovaries for embryo transfer or in vitro embryo production.